THE ROLE OF THE MOSQUE IN EDUCATING HARMONIOUS FAMILIES (A STUDY AT JOGOKARIYAN MOSQUE, MANTRIJERON) - Risky, Abu; Suyadi, S; Husain, Andi Musthafa (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The mosque is a place of worship for Muslims that has a strategic role in the advancement of Islamic civilization. History has demonstrated the multifunctional roles of mosques. Mosques are not only places for performing prayers but also serve as centers for education, religious study, military training, and various socio-economic functions. The Prophet Muhammad (PBUH) exemplified the multifunctional nature of mosques. To date, family education programs have been implemented by the government, and society continues to develop models of harmonious family education through various media, including mosques. The purpose of this research is to describe the role of the mosque in educating harmonious families at Jogokariyan Mosque. The focus of this research is the Jogokariyan Mosque in Mantrijeron, Yogyakarta, which, according to the author, has implemented efforts towards harmonious family education. This research is categorized as qualitative research with its inherent characteristics. The data collection methods used include interviews, observations, and document studies. To analyze the collected data, this research employs qualitative data analysis with the following steps: a) data reduction, b) data display, and c) conclusion drawing and verification. The results of this research conclude that Jogokariyan Mosque has demonstrated its role or contribution in efforts towards harmonious family education, not only for the community around the mosque but also for other surrounding communities. The mosque's roles include aspects of worship education, improving the quality of Islamic education, health aspects, economic empowerment, and the relationship patterns between families and the environment. Among these five aspects, worship education receives the most attention from the mosque's management. This highlights that the primary function of the mosque is to foster obedience and devotion to Allah SWT.